Pengaruh penerapan model pembelajaran make a match berbasis media visual poster terhadap hasil belajar siswa - Wiwin Mistra Jeniwanti; Edy Herianto; Bagdawansyah Alqadri (Journal of Education, Cultural and Politics, 2026)
This study aims to determine the effect of implementing a poster-based make-a-macth learning model on eitghth-grade students’ learning participation in Pancasila Education at SMPN 10 Mataram. This study usd a quantitative approach with a quasi-experimental design an d a non-equivalent control group design. The study population was all eighth-grade students at SMPN 10 Mataram, with a sample size of 40 students divide into two classes: a control class and an experimental class. Data collection used a questionnaire that had been tested for validity dan reliability. The validity test resulst showed 42 valid statements, which were then analyzed according to their content depth and breadth of context, resulting in 36 statements used in the questionnaire. The reliability test showed a Cronbah’h Alpha value of 0.9103, indicating a reliable instrument. The conclusion of this study indicates that implementing a poster-based make-a-macth learning model did not significanly impact student learning participation. This can be influenced by several factors, such as students who are not yet accustomed to the cooperative learning model, less condusive classroom condition, and the quality of students responses when filling out the questionnaire.